2019
DOI: 10.1111/jorc.12273
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a tailored education programme: renal transplant recipients’ experiences

Abstract: 2019). Implementing a tailored education programme: renal transplant recipients' experiences. Journal of Renal Care XX(XX),1-9. S U M M A R YBackground: Patient-centred education is a key element in the care of patients undergoing kidney transplantation. We implemented a tailored, evidence-based education programme for the post-transplant phase. Objective: The aim of the study was to explore renal transplant recipients' experiences of participating in a new, tailored, evidence-based education programme. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…[ 35 ] In a study of renal transplant recipients' experiences of participating in a new, tailored, evidence-based education program, it was found that they feel more satisfied with receiving individualized education. [ 36 ] On the other hand, participants stated that facilitating the processes using new technologies, teamwork education, and patient and family accessibility is necessary to achieve PFCE. Studies have shown that using remote technology-based education such as websites, smartphone applications, and social networks as a strategy has increased knowledge, medication adherence, and patient education effectiveness in transplanted recipients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] In a study of renal transplant recipients' experiences of participating in a new, tailored, evidence-based education program, it was found that they feel more satisfied with receiving individualized education. [ 36 ] On the other hand, participants stated that facilitating the processes using new technologies, teamwork education, and patient and family accessibility is necessary to achieve PFCE. Studies have shown that using remote technology-based education such as websites, smartphone applications, and social networks as a strategy has increased knowledge, medication adherence, and patient education effectiveness in transplanted recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation is a replacement treatment alternative for patients with end‐stage kidney disease (Andersen et al, 2019). However, despite the benefits of renal transplantation, recipients encounter several problems including renal toxicity (Walsh & Dinavahi, 2016), hypertension (Severova‐Andreevska, Danilovska, Sikole, Popov, & Ivanovski, 2019), new‐onset diabetes mellitus (Nie et al, 2019), dyslipidemia and hyperuricemia following with the immunosuppressive drugs (Robledo et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transplantation is one of the miraculous achievements of modern medicine for patients with end‐stage kidney disease as it improves organ failure‐related symptoms (Been‐Dahmen et al, 2018), long‐term survival rates and quality of life (Jain et al, 2019; Veater & East, 2016). However, renal transplant patients experience new challenges of managing their new grafts, using long‐term immunosuppressants, and adapting to various daily restrictions (Andersen, Wahl, Engebretsen, & Urstad, 2019). Moreover, they must cope with emotional distress, self‐care management and social interactions (Been‐Dahmen et al, 2018; Veater & East, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the fourth in a row within a broader implementation project aiming to examine the implementation of the new education program, from different angles and in different phases utilizing different study designs [16,[27][28][29]. The focus of the current study was whether the positive effects of the randomized controlled trial (RCT) intervention could be recaptured in a long-term perspective.…”
Section: Introductionmentioning
confidence: 99%